Widening access of black students into physiotherapy programmes in the South Africa - N. P. Mbambo (AOSIS, 2004)
Access to learning and the provision of equal opportunities for success and progression to the previously disadvantaged communities is addressed extensively in the Education White Paper 3. While historically white universities have invested some effort to diversify the racial composition of their students, physiotherapy departments at these universities do not reflect a change in student demographics. The purpose of this article is to address the concept of widening access into physiotherapy education within the  context of transformation in higher education. The article examines the history of education in the past dispensation, the policies that have been put in place to redress the educational inequalities caused by the past dispensation and makes suggestions as to how universities can react to them. The literature that has examined the relationship between entry requirements and the success of students within the chosen profession is also outlined.  The article concludes with recommendations for a way forward for physiotherapy in addressing some of the issues related to student selection.